REDUCING WAVE SHOALING OVER A LINEAR TRANSITION BOTTOM WITH A SUBMERGED POROUS BREAKWATER - Nathanael Hery, Owen
Wave shoaling phenomenon caused by changes in the seabed morphology can cause significant damage to coastal areas. One way to dispel the phenomenon is by forming a breakwater construction. We will examine the effect of porous breakwater on shoaling phenomena over a linear transition bottom. There are two types of problems reviewed in this study, namely the wave transmission coefficient and resonance phenomena. Analytically, we will find the value of wave transmission coefficient and basin’s natural period using a modified shallow water equation model for the two-layer case. The basin’s natural period value is a parameter needed to observe the resonance phenomenon. Afterwards, we will do several simulations using numerical scheme which is derived from the finite volume method on a staggered grid. Variations due to linear transition bottom are reviewed together along the implementation of dumping coefficients from the porous breakwater to reduce the effects of emerging phenomena, one of which is the resonance phenomena.